Influence of social media on shaping tourists’ preferences - Zawadka, Jan; Liwińska, Monika (Turystyka i Rozwój Regionalny, 2022)
The aim of this article is to present the role of social media and influencers (being an inseparable element of these media) in shaping tourists’ preferences. The research was conducted from March to May 2021. The method of research was a diagnostic survey with the use of the questionnaire technique. The answers were obtained from 127 adults. Based on the results, it can be concluded that social media are a popular and willingly used source of inspiration when planning a tourist trip and play a significant role in creating the image of a tourist destination. Influencers significantly contribute to the growth of interest in the destinations they promote. However, they are not treated as a source of reliable and credible information.